(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This work is a logical continuation of the authors’ cycle of works devoted to construction of a mathematical model of the unloading process of cuttings from a slotted hopper. The purpose of the paper is a theoretical justification of the movement of an array of cuttings during gravity unloading. The article proposes consideration of the process of unloading the energy willow cuttings from the point of view of hydrodynamic multiphase systems. It is suggested to consider the set of cuttings as a pseudo-fluid consisting of two phases: discrete (cuttings) and continuous (air). Each of these phases can be considered as a continuous environment. Under such conditions, the task is reduced to consideration of the cuttings' discharge as the movement of a viscous non-contacting pseudo-liquid. Under such assumptions, the velocity field of the set of cuttings can be characterized by the Navier-Stokes equation, the solution of which will allow forming of an algorithm for building a mathematical model of the motion of such pseudo-fluid and moving to the calculation equations of the motion with initial and boundary conditions.